Microbiological assessment for potable water - Paudel, Kriti; Basi-Chipalu, Shradha (Scientific World, 2022)
Drinking water quality assessment in Kathmandu valley has always been crucial with reference to public health importance. The objective of this study was to assess the quality of drinking water with respect to physiochemical and microbiological parameters. A total of 63 random water samples were collected from different sources like stone spout, tap, well, boring, hand pumps and jar from different wards of Kageshwori Manohara Municipality, Kathmandu. The study was carried out for 6 months from January to July, 2019. The pH of the samples was in the range of 6.5-7.2, temperature 5-19 °C, chloride 0-96.56 mg/L, nitrate 0-5.4 mg/L and iron 0-1.1 mg/L. The physicochemical parameters including pH, temperature, chloride, nitrate of the samples were found to lie within the WHO guideline value except iron where 4 (6.34%) samples including 2 tap, 1 boring and 1 well exceeded WHO guideline. The bacteriological analysis of water samples revealed the presence of total coliform in 35 (55.56%) out of 63 samples, among which 8 (12.69%) were found to have faecal coliform. Furthermore, Salmonella spp. was isolated from 1 out of 63 samples. However, all the samples were free of Shigella spp. and Vibrio spp. It was found that most of the water samples were non potable as total and faecal coliform exceeded the WHO guideline value of drinking water.